1959
DOI: 10.1111/j.1151-2916.1959.tb13600.x
|View full text |Cite
|
Sign up to set email alerts
|

Subsolidus Reactions in the System Fe2O3‐ TiO2

Abstract: A study has been made of the binary system FenOt-TiO,, by solid-state reactions under dry and hydrothermal conditions. Under dry conditions only one binary compound, pseudobrookite (FeZOa-TiOz), was formed and no evidence of solid solution on either side of this compound at temperatures up to 1200OC. was obtained.The system under these conditions is a simple binary with a single binary compound. Under hydrothermal conditions of 300OC. and 1200 Ib. per sq. in. the system is apparently also binary, with a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1960
1960
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…Pseudobrookite, Fe 2 TiO 5 , is the only phase reported to a tetragonal unit cell ((44) PDF 39-810); however, to our knowledge no detailed structural study or other form in the TiO 2 -Fe 2 O 3 binary system (23,35,36). The crystal structure of pseudobrookite features Ti 4ϩ in octahe-reports of this phase have subsequently appeared in the literature.…”
Section: Introductionmentioning
confidence: 87%
“…Pseudobrookite, Fe 2 TiO 5 , is the only phase reported to a tetragonal unit cell ((44) PDF 39-810); however, to our knowledge no detailed structural study or other form in the TiO 2 -Fe 2 O 3 binary system (23,35,36). The crystal structure of pseudobrookite features Ti 4ϩ in octahe-reports of this phase have subsequently appeared in the literature.…”
Section: Introductionmentioning
confidence: 87%
“…Buddington and Linsley, 1964) and is only partially successful under hydrothermal conditions (Karkhanavala, 1959;Karkhanavala and Momin, 1959). Under dry conditions and high temperatures (e.g.…”
Section: The Effect Of Aging At Ph 12 and 70~ For 70 Daysmentioning
confidence: 99%
“…in chemical petrology). Karkhanavala and Momin (1959) hydrothermMly crystalized small amounts of pseudorutile at 300~ and 1200 psi and concluded that it was "not the product of atmospheric oxidation." These results are considered to be of little value in determining the conditions and type of Fe-Ti phase which will form during the alteration of titaniferous primary minerals under earth surface conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, a Gibbs energy description of the rutile polymorph has been incorporated in the database (Table ). Intermediate stoichiometric phases for the BaO–TiO 2 , Cs 2 O–TiO 2 , FeO–TiO 2 , and Fe 2 O 3 –TiO 2 systems were included in the database. In addition, Amoroso et al observed the formation of the BaFe 12 O 19 and FeAl 2 O 4 phases.…”
Section: Thermodynamic Modeling and Optimizationmentioning
confidence: 99%